Red blood cell lipid distribution in the pathophysiology and laboratory evaluation of chorea-acanthocytosis and McLeod syndrome patients - Cloos, Anne-Sophie; Ghodsi, Marine; Stommen, Amaury; Recktenwald, Steffen M.; Kaestner, Lars; Danek, Adrian; Spranger, Adrian; Hermann, Andreas; Peikert, Kevin; Tyteca, Donatienne (Frontiers in Physiology, 2025)
The core neuroacanthocytosis syndromes, i.e., chorea-acanthocytosis/VPS13A disease (ChAc) and McLeod syndrome/XK disease (MLS), are respectively due to mutations in VPS13A and XK genes and share similar manifestations including the formation of acanthocytes. We previously showed by lipidomics of red blood cells (RBCs) from ChAc patients slight lipid changes compared to healthy controls. We here evaluated the consequences for RBC morphology, deformability, cytoskeleton and membrane lipid transversal and lateral distribution in five patients with ChAc and two patients with MLS. Compared to healthy donors, the two patient cohorts showed a strong increase of abnormal RBCs including acanthocytes and spheroechinocytes, a decrease in RBC projected surface area and deformability, and a rise in spectrin density. The abundance of cholesterol-enriched domains and the proportion of RBCs with ceramide-enriched patches were also increased while phosphatidylserine surface exposure was slightly decreased. In contrast, the abundance of sphingomyelin-enriched domains was poorly affected. At the individual level, patients showing the highest cholesterol-enriched domain abundance exhibited the highest number of RBCs with ceramide-enriched patches, compatible with RBC maturation defects, whereas patient RBCs exhibiting the highest spectrin membrane density showed the strongest loss of RBC projected surface area and the lowest abundance of sphingomyelin-enriched domains, consistent with RBC membrane alterations. Our study indicated that abnormal RBCs were associated with lipid distribution and cytoskeleton impairments, which appeared to result from both RBC maturation defects and membrane alterations. Moreover, the extent of lipid distribution alteration is well correlated with laboratory parameters typically altered in neuroacanthocytosis and could present an added value in neuroacanthocytosis syndrome evaluation.